Implementasi Perwal Nomor 111 Tahun 2022 tentang Pembatasan Pennggunaan Kantong Plastik di Kota Tangerang - Samuel Gregorio Lumban Tobing; Yuwanto Yuwanto (Journal of Politic and Government Studies, 2026)
The implementation of restrictions on plastic bag usage in Tangerang City has been regulated under Mayor Regulation No. 111 of 2022 concerning the Limitation of Plastic Bag Usage. This study aims to examine how policy implementers carry out the regulation and to analyze the supporting and inhibiting factors in reducing plastic bag usage in Tangerang City. Using a qualitative case study approach with descriptive analysis through interviews and observations, the findings reveal that the implementation of plastic bag restrictions has not been fully effective or optimal. The policy implementation is analyzed using George C. Edward III’s four indicators of policy implementation. Communication emerges as the supporting factor, while resources, disposition, and bureaucratic structure act as inhibiting factors. The study recommends that policy implementers establish a monitoring team, allocate sustainable funding, and intensify public outreach on the use of environmentally friendly shopping bags.